2021
DOI: 10.3390/biology10121306
|View full text |Cite
|
Sign up to set email alerts
|

Beta vulgaris L. (Beetroot) Methanolic Extract Prevents Hepatic Steatosis and Liver Damage in T2DM Rats by Hypoglycemic, Insulin-Sensitizing, Antioxidant Effects, and Upregulation of PPARα

Abstract: The present study examined if methanolic beetroot extract (BE) could prevent dyslipidemia and hepatic steatosis and damage in a type-2 diabetes mellitus (T2DM) rat model and studied some mechanisms of action. T2DM was induced in adult male Wistar rats by a low single dose of streptozotocin (STZ) (35 mg/kg, i.p) and a high-fat diet (HFD) feeding for 5 weeks. Control or T2DM rats then continued on standard or HFDs for another 12 weeks and were treated with the vehicle or BE (250 or 500 mg/kg). BE, at both doses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…resulting in scientific investigations focused on the development of novel agents with anti-glycation effects with the ability to prevent and alleviate diabetes complications. Due to the traditional usage of chard as antidiabetic and supported by in vivo experiments [7]. we studied CH extract as a potential agent against BSA glycation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…resulting in scientific investigations focused on the development of novel agents with anti-glycation effects with the ability to prevent and alleviate diabetes complications. Due to the traditional usage of chard as antidiabetic and supported by in vivo experiments [7]. we studied CH extract as a potential agent against BSA glycation.…”
Section: Resultsmentioning
confidence: 99%
“…flavescens has been used in traditional medicine for its antibacterial and hypoglycemic properties (5). Contains phytochemicals that have beneficial activities including anti-inflammatory, antioxidant, and antiproliferative effects (6) The antidiabetic potential of B. vulgaris leaves was reported in diabetic Wistar rats induced with streptozotocin (STZ) and a high-fat diet (HFD) demonstrated that prevents it liver damage and hepatic steatosis by its insulin-sensitizing, and hypoglycemic properties and their capacity to upregulate antioxidants and PPARα (7). According to the literature, there is no report of in vitro anti-glycation activity of B. vulgaris leaves thus, our investigation aimed to determine the anti-glycation effect of the leaves extracts of B. vulgaris by using a battery of invitro assays.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that treatment of Wistar rats with type 2 diabetes induced by STZ with methanolic beetroot extract and a high-fat diet reduced serum and hepatic levels of cholesterol, triglycerides, and free fatty acids, which was associated with downregulated transcription of SREBP1/2 and stimulation of PPARα [ 55 ]. Congruent with these results, we observed that the hypolipidemic effects of beetroot in SHR-CRP rats were associated with increased fatty acid oxidation in the skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained result agreed with that of Lee et al [37], who observed that involving lyophiliyzed beetroot leaves in rats receiving a high cholesterol diet reduced the gained weight significantly compared to the control. Similarly, Al-Harbi et al [38] noticed that beetroot stem extract reduced the weight in diabetic rats fed with a high-fat diet.…”
Section: Weight Gainingmentioning
confidence: 91%